Genetic lesions of type i interferon signalling in human antiviral immunity (2020)
The concept that type I interferons (IFN-I) are essential to antiviral immunity derives from studies on animal models and cell lines. Virtually all pathogenic viruses have evolved countermeasures to IFN-I restriction, and genetic loss of viral IFN-I antagonists leads to virus attenuation. But just how important is IFN-I to antiviral defence in humans? The recent discovery of genetic defects of IFN-I signalling illuminates this and other questions of IFN biology, including the role of the mucosa-restricted type III IFNs (IFN-III), informing our understanding of the place of the IFN system within the concerted antiviral response. Here we review monogenic lesions of IFN-I signalling pathways and summarise the organising principles which emerge.